Antifungal discovery. (October 2022) - Robbins, Nicole; Cowen, Leah E
Abstract : Fungi have a profound impact on human health, leading to billions of infections and millions of deaths worldwide each year. Exacerbating the public health burden is the continued emergence of drug-resistant fungal pathogens coupled with a dearth of treatment options to combat serious infections. Despite this health threat, scientific advances in chemistry, genetics, and biochemistry methodologies have enabled novel antifungal compounds to be discovered. Here, we describe current approaches for the discovery and characterization of novel antifungals, focusing on the identification of novel chemical matter and elucidation of the cellular target of bioactive compounds, followed by a review of the most promising emerging therapies in the antifungal-development pipeline. Highlights: Fungi have a serious impact on human health, causing millions of deaths worldwide. Scientific advances have enabled the discovery of novel antifungals. This review describes the discovery and characterization of novel antifungals. We summarize promising emerging therapies in the antifungal pipeline.